Full length sequencing reveals novel transcripts of detoxification genes along with related alternative splicing events and lncRNAs in Phyllotreta striolata. - Guang Mao Shen; Shi Yuan Ou; Chu He; Jie Liu; Lin He (PLoS ONE)
The striped flea beetle, Phyllotreta striolata (Fabricius), damages crops in the Brassicaceae. The genetic data for this pest are insufficient to reveal its insecticide resistance mechanisms or to develop molecular markers for resistance monitoring. We used PacBio Iso-Seq technology to sequence the full-length transcriptome of P. striolata. After isoform sequence clustering and removal of redundant transcripts, a total of 41,293 transcripts were obtained, and 35,640 of these were annotated in the database of gene products. Structure analysis uncovered 4,307 alternative splicing events, and 3,836 sequences were recognized as lncRNAs. Transcripts with the complete coding region of important detoxification enzymes were further classified. There were 57 transcripts of P450s distributed in CYP2, CYP3, CYP4, and Mito CYP clades, 29 transcripts of ESTs from 4 functional groups, 17 transcripts of GSTs classified into 5 families, 51 transcripts of ABCs distributed in 6 families, and 19 transcripts of UGTs. Twenty-five lncRNAs were predicted to be regulators of these detoxification genes. Full-length transcriptome sequencing is an efficient method for molecular study of P. striolata and it is also useful for gene function analysis.